The effects of photoperiod on testes in rat: A morphometric and immunohistochemical study - Kus, I; Akpolat, N; Oner, H; Ayar, A; Pekmez, H; Ozen, OA; Sarsilmaz, M (Maghira & Maas Publications, 2003)
OBJECTIVE: The aim of this study was to examine the effects of photoperiod on testes in rat. DESIGN: For this purpose 21 male Wistar rats were used. Animals were divided into three groups. Control rats in group I were kept under 12 hrs light: 12 hrs dark conditions (12L: 12D) for 10 weeks. Animals in group II were exposed to long photoperiods (18L: 6D), while rats in group III were exposed to short photoperiods (6L: 18D) for 10 weeks. At the end of the experiment, all animals were killed by decapitation and blood samples were obtained. Serum testosterone levels were determined with the use of a chemiluminescent enzyme immunoassay. The testes of all rats were removed and weighed. Testicular tissue was processed semiquantitative evaluation of immunohistochemical testosterone staining. Intensity of immunostaining was determined on a scale between 0 (no staining) and 5 (heavy staining). For morphometric comparison, diameters of seminiferous tubules in each group were measured. RESULTS: In rats exposed to long photoperiods, testicular weights, diameters of seminiferous tubules and serum testosterone levels were significantly increased as compared to those in control rats. Whereas, exposure of rats to short photoperiods resulted in significantly decrease of testicular weights, diameters of seminiferous tubules and serum testosterone levels as compared to those in control rats and rats maintained in long photoperiods. Immunostaining of testosterone was moderate (3+) in control rats, heavy (5+) in rats exposed to long photoperiods and minimal (1+) in rats exposed to short photoperiods. CONCLUSIONS: The results of our study indicate that testicular functions increase after exposure to long photoperiods and decrease after exposure to short photoperiods.
Keywords: photoperiod; testes; immunohistochemistry; rat